2020
DOI: 10.1128/mra.01450-19
|View full text |Cite
|
Sign up to set email alerts
|

Complete Genome Sequence of Gordonia sp. 135, a Promising Dibenzothiophene- and Hydrocarbon-Degrading Strain

Abstract: Gordonia sp. strain 135 is a promising dibenzothiophene-desulfurizing and hydrocarbon-degrading bacterium. It can utilize dibenzothiophene as the sole sulfur source. The genome of strain 135 was completely sequenced; it consists of a 5,039,827-bp circular chromosome and a 164,963-bp circular plasmid.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 11 publications
0
11
0
Order By: Relevance
“…The genome of the strain was sequenced and completely assembled [ 16 ]. The Gordonia alkanivorans 135 genome consists of a 5,039,827 bp circular chromosome (GC content of 67.44 %, NZ_CP046257) and a 164,963 bp circular plasmid, namely, pG135 (GC content of 64.58 %, NZ_CP046258).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The genome of the strain was sequenced and completely assembled [ 16 ]. The Gordonia alkanivorans 135 genome consists of a 5,039,827 bp circular chromosome (GC content of 67.44 %, NZ_CP046257) and a 164,963 bp circular plasmid, namely, pG135 (GC content of 64.58 %, NZ_CP046258).…”
Section: Resultsmentioning
confidence: 99%
“…The microorganism used in this study was Gordonia alkanivorans 135 isolated in our laboratory [ 16 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…# SQK-RBK00), MiSeq Reagent Kit v3 (cat. # MS-102-3003; 2 × 300 bp), NEBNext Ultra DNA Library Prep Kit (New England Biolabs, USA); Programs, Guppy 3.2.4, FastQC ( http://www.bioinformatics.babraham.ac.uk/projects/fastqc ), SPAdes 3.15.2 [26] , the Flye assembler 2.6 [27] , Bowtie2 2.3.5.1 [28] , Pilon 1.23 [29] , the Tablet [30] software; and Equipments, MinION sequencer with an R9.4.1 flow cell (Oxford Nanopore Technologies, UK), MiSeq System (Illumina, USA) were used as described earlier [31] .…”
Section: Methodsmentioning
confidence: 99%
“…We have previously isolated two Gordonia strains, Gordonia amicalis 1D and Gordonia alkanivorans 135, which utilize DBT as the sole sulfur source for growth [ 37 , 38 , 39 ]. Genome sequencing showed that these strains had no dsz operon, required for the 4S pathway of thiophene desulfurization.…”
Section: Introductionmentioning
confidence: 99%